A New Theoretical Model of Rock Burst-Prone Roadway Support and Its Application. (23rd February 2021) - Gao, Mingshi; He, Yongliang; Xu, Dong; Yu, Xin
Abstract : A rock burst usually causes a roadway collapse or even an instant blockage. When the deformation energy accumulated in the surrounding rock exceeds the minimum energy required for the dynamic destruction of the surrounding rock of a roadway, a rock burst accident will occur. According to statistics, 85% of rock burst accidents occur in roadways. This paper establishes a strong-soft-strong structural model for the rock burst stability control of the surrounding rock of a roadway, and the anti-impact and antiseismic mechanisms of the mechanical model are analysed. The strength, stress transfer, deformation, and energy dissipation characteristics of the strong-soft-strong structure are studied. The stress criterion and energy criterion of rock burst failure in small internal structures are derived for roadway support design. The support scheme of "anchor cable active support + hydraulic lifting support + soft structure energy absorption" is proposed. A steel pipe can be inserted into a borehole drilled into the small internal structure to realize the proposed innovative protection technology for small internal structures by creating a soft structure that can release, absorb, and transfer the pressure by repeatedly cracking the coal and rock mass. The innovation of cracking technology for soft roadway structures has been realized. The roadway tested with this strong-soft-strong enhanced surrounding rock control technology met the production requirements during the mining period. The field test was successful, and the expected support effect was achieved. This work provides a reference for roadway support under similar conditions and can be popularized and applied.